Pembelajaran Di Era Emergency Remote Teaching: Analisis Faktor Penghambat Partisipasi Diskusi Online Mahasiswa dan Strategi untuk Mengatasinya - Ardiansyah, Arief; Meillynia, Bunga Vanda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Online discussion methods are widely applied in various educational institutions, especially in Islamic universities. However, the popularity of this method is not accompanied by the students' enthusiasm for following it. This study endeavors to explicate the factors preventing students from contributing in online discussions and techniques to overcome them. This research is a study that uses library research techniques. The present investigation entails a series of sequential phases, including determining the topic of study, finding and selecting various literature related to the topic, reviewing the literature, and compiling the literature into a study. The present study employed content analysis techniques to scrutinize data derived from diverse literary sources. The outcomes of the study indicate that there are six crucial factors that impede students from participating in online discussions, including (a) not understanding the importance of virtual discussion, (b) the attitude or habits of the instructor or learner, (c) personal character, (d) not understanding what to contribute, (e) low critical thinking skills, and (f) lack of time. Instructors must know these barriers and implement strategies to make online discussion forums exciting and compelling. The present study findings have dual implications, practically and theoretically. Practically, this study has the potential to serve as a guiding framework in conducting the online discussion learning method. Theoretically, this study can add to the scientific treasures in discussion learning methods in universities and can be a foundation for researchers pursuing additional investigation within the identical domain.